DESIGN OF DERMA STICKS OF ANDROGAPHIS PANICULATA FOR THE TREATMENT OF GYNAECOLOGICAL SKIN DISORDERS - K., Savita Sonawane; Rao, Purushotham (International Journal of Current Pharmaceutical Research, 2018)
Objective: Vaginal candidiasis are often painful and uncomfortable and can include intense itching, irritation, vaginal discharge and dysuria. Gynaecological skin disorders referring to inflammatory and infectious conditions affecting the vaginal mucosa and vulvitis often accompanies vagina pain, itching and burning sensation. Herbal therapy is gaining popularity of women on account of it’s reduced side effect and restoration of the normal vaginal flora. Plants reported to possess activity or used in traditional systems of medicine for prevention and treatment of vaginitis. Therefore, it was found essential to find an alternative to counter all the above disadvantages effectively and hence in the present work, formulation and development of medicated sticks has been planned with the herbal drug Androgaphis Paniculata which is very well known for the anti bacterial and anti fungal activity. Methods: The preparation and characterization of medicated sticks was carried out in four phases. Phase I studies includes preparation of medicated derma sticks using the ointment bases with varied concentrations of waxes. Phase II studies involves characterization of prepared medicated derma sticks like weight, thickness and length. Phase III studies involves stability studies of prepared formulations. Phase IV Studies involves anti microbial studies by zone inhibition method. .Phase V: Primary skin irritation studies carried out on rabbits and guinea pigs and in healthy human volunteers showed no sensitization and edema on skin after 72 h of application. Results: The results of present study revealed that the prepared medicated sticks of Androgaphis Paniculata are convenient, equally effective, without any contamination chances on application and free from skin irritation. Conclusion:The present work is a unique piece of contribution to the drug industry. The results will be useful to industry RandD for further investigations. The continuation of these work clinical studies is in progress. Objective: Vaginal candidiasis are often painful and uncomfortable and can include intense itching, irritation, vaginal discharge and dysuria. Gynaecological skin disorders referring to inflammatory and infectious conditions affecting the vaginal mucosa and vulvitis often accompanies vagina pain, itching and burning sensation. Herbal therapy is gaining popularity of women on account of its reduced side effect and restoration of the normal vaginal flora. Plants reported to possess activity or used in traditional systems of medicine for prevention and treatment of vaginitis. Therefore, it was found essential to find an alternative to counter all the above disadvantages effectively and hence in the present work, formulation and development of medicated sticks have been planned with the herbal drug Androgaphis Paniculata which is very well known for the antibacterial and antifungal activity. Methods: The preparation and characterization of medicated sticks were carried out in four phases. Phase I studies include preparation of medicated derma sticks using the ointment bases with varied concentrations of waxes. Phase II studies involve characterization of prepared medicated derma sticks like weight, thickness and length. Phase III studies involves stability studies of prepared formulations. Phase IV Studies involves antimicrobial studies by zone inhibition method. .Phase V: Primary skin irritation studies carried out on rabbits and guinea pigs and in healthy human volunteers showed no sensitization and edema on the skin after 72 h of application. Results: The results of present study revealed that the prepared medicated sticks of Androgaphis Paniculata are convenient, equally effective, without any contamination chances on the application and free from skin irritation. Conclusion: The present work is a unique piece of contribution to the drug industry. The results will be useful to industry R&D for further investigations. The continuation of these work clinical studies is in progress.